Layanan Konseling Individual untuk Mengatasi Kecemasan dan Ketegangan pada Siswa dengan Teknik Relaksasi Otot Kelas IX di SMP Negeri 4 Aimere (Indonesian Journal of School Counseling: Theory, Application, and Development, 2022)
The purpose of this study were (1) to determine the types of anxiety a experienced by students, (2) factors that cause anxiety asiswa, (3) counseling approach applied   Teacher   BK inovercoming  the  anxiety  of  students,  and (4)   to   know   the  assessment  of students to counseling services that do counseling teacher at the   school   as   perceived   by   the   counseling teacher at the school. This research is qualitative obtained  from the  informant  and  the  subject's behavior is  observed. Instruments  are students and teachers BK with a sample size 3 students and 1 teachers BK SMP NEGERI 4 AIMERE Data collection through direct interview to the informant. The results showed that (1) the types of anxiety experienced by students who studied are anxiety is psychological in the form of dizziness,  anxiety,  and  could  not  sleep,  (2) factors that cause anxiety students are learning achievement that is not in line with expectations, could   not  adjust   to   the   subject,   had   no educational aspirations, and worried about the future,   (3)   a tutor   in   overcoming   anxiety academic in students, not using the obvious approach in dealing swith students who have anxiety problems of academic, approach still partial,  incidental routines,  and  tend  to  be behavioristik, (4) counseling service approach used   by   teachers   in   handling   anxiety   BK students have not been effective, both in the eyes of students and teachers BK itself.so that   the BK teacher conduct individual counseling by using the relaxation techniques